If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + 12 = 7 Reorder the terms: 12 + 4a = 7 Solving 12 + 4a = 7 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 4a = 7 + -12 Combine like terms: 12 + -12 = 0 0 + 4a = 7 + -12 4a = 7 + -12 Combine like terms: 7 + -12 = -5 4a = -5 Divide each side by '4'. a = -1.25 Simplifying a = -1.25
| 4(x-9)=x-15 | | 4(y-8)=8 | | m/3-6 | | 8h^2-50= | | 4/9:134/72 | | 9+3y-2yt=14 | | x(2x+7)= | | 11-8b=-5-4b | | 4a+12=-16 | | 4(y-4)=2(y+25)-4 | | 10x-18=x+63 | | 5Y+9=8Y-6 | | -8+9n=10 | | 7m-6=-104 | | 7x+60=x+60 | | (4x^2+4x+1)-(4x^2+2)=8x+16 | | 3-(5x-1)/10=(x-1)/5-(x-3)/2 | | 5r=-1 | | 5r=-2 | | 7-6a=1-4a+a | | 4u+13=65 | | 4p-4=56 | | 9x-90=4x+55 | | A=49sqin | | 5(x-5)+5=-50 | | 6b+3=4b+5 | | 4/k=6=11 | | f(x)=6x^2+5x+3 | | 21/3x5-11= | | 1/(2sqrtx)=0.1111111111 | | -3(2x+6)-4+5x=4(x-5)+9-2x | | 3(x-3)-20=-23 |